Warthin-like papillary thyroid carcinoma: a case report and comprehensive review of the literature - Missaoui, Abdel Mouhaymen; Hamza, Fatma; Belabed, Wafa; Mellouli, Manel; Maaloul, Mohamed; Charfi, Slim; Jardak, Issam; Sellami-Boudawara, Tahya; Rekik, Nabila; Abid, Mohamed (Frontiers in Endocrinology, 2023)
Background: Papillary Thyroid Carcinoma (PTC) is the most frequent endocrine malignancy with a variety of histological presentations. Warthin-like Papillary Thyroid Carcinoma (WLPTC) is an uncommon neoplasm that is recognized as a distinct subtype of PTC in the WHO classification of thyroid tumors. In this report, we present a novel case of WLPTC in a female patient and provide an in-depth review of the available literature on its clinical, pathological, and therapeutic characteristics.Case presentation: A 27-year-old female patient was referred for neck swelling. Ultrasound showed two suspicious thyroid nodules leading to a thyroidectomy. She was diagnosed with intermediate-risk bifocal foci of classic PTC and WLPTC, arising from a background of chronic lymphocytic thyroiditis (CLT). This pT1b(m) N1b M0 malignancy was treated with adjuvant isotopic ablation and suppressive thyroxine therapy. The 1-year outcomes were favorable.Literature Review: It covered articles published from 1995 to 2022, by searching PubMed and Google Scholar using specific terms. Out of 148 articles reviewed by two authors, 25 relevant articles were selected, including 13 case reports and 12 case series. The study included 150 cases of WLPTC. Data related to clinical presentation, imaging, histological features, management, and outcomes, were extracted. The mean age of diagnosis was 39 years, with a female predominance. The most common clinical presentation was neck swelling. Thyroid autoimmunity was positive in 71.6% of patients. Lymph node metastases were present in 28% of cases, with no reported distant metastases. Overall, the outcomes were favorable.The hallmark histological features of WLPTC are papillae lined with oncocytic tumor cells with papillary nuclear changes and lymphoid stroma. WLPTC is almost constantly associated with CLT. The management of WLPTC aligns with that of classic PTC with comparable stage and risk category, often resulting in favorable outcomes.